Good governance in town - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Municipalities and Community Participation. A Sourcebook for Capacity Building By J Plummer, Earthscan Publications, 2000. 146 pp. ISBN 185383744X GBP 20 Euro 31.35